CONTENTS OF PREPARATORY PREPARATION PREPARATION IN GALICHYNY AT THE BEGINNING OF XX CENTURIES - Fedorovych, Anna (Mountain School of Ukrainian Carpaty, 2019)
The content of the training of preschool children was paid insufficient attention, which determined the purpose of our article. Its improvement should be based on the pedagogical experience gained during the birth of the education system of preschool specialists. Methods: аnalysis and synthesis, systematization and generalization of theoretical data presented in scientific literature. On the basis of the analysis of the system of preschool education and the peculiarities of the training of educators in Halychina at the beginning of the 20th century, the content of teaching students in the teacher's seminaries, on courses of training and in pedagogiyas is considered in the article; preschool institutions are needed specialists of different specialties (educators, psychologists, assistants, doctors) are proven in the article; in the period under study we developed a comprehensive approach to the content of the training of preschool teachers, students underwent extensive practical and theoretical training (they studied hygiene, psychology of the child, experimental psychology and pedagogy, technique by F. Frebel's, methods, movement with the basics of medicine, etc.) are accented. At the beginning of the 20th century in Halychina the practical and theoretical foundations of preschool pedagogical education have been formed. The content of the training of preschool workers was gradually supplemented and provided: spiritual, psychological, pedagogical, methodological, health and hygienic components, the essence of which requires further research.